Effect of Lauric Acid on the Thermal and Mechanical Properties of Polyhydroxybutyrate (PHB)/Starch Composite Biofilms - Joemer A. Adorna; Camelle Kaye A. Aleman; Ian Lorenzo E. Gonzaga; Jamela N. Pangasinan; Kim Marie D. Sisican; Van Dien Dang; Ruey-An Doong; Ruby Lynn G. Ventura; Jey-R S. Ventura (International Journal of Polymer Science)
Polyhydroxybutyrate (PHB) is a biopolymer of natural origin, one of the suitable alternatives for synthetic plastics. However, pure PHB has a high production cost, is relatively brittle, and has poor processability, hence its limited application. Combining PHB with biomass fillers and plasticizers can significantly improve the properties of the polymer, leading to its commercial usage. In this study, PHB was incorporated with starch (S) as a cheap biomass filler and lauric acid (LA) as a potential plasticizer. The PHB/S/LA composites were prepared using a modified solvent casting method with the incremental addition of LA. The PHB/S ratio was maintained at a ratio of 80/20 (w/w). Physicochemical characterization via EDS, XRD, and FTIR proved that the composite components have blended through nucleation and plasticization processes. The morphology of the PHB/S blends was found to be a heterogeneous matrix, with decreased inhomogeneity upon the addition of LA in the composite. Thermal characterization done by TGA and DSC showed that the thermal properties of PHB/S films improved with the addition of LA. Mechanical tests (UTM) proved that the elastic strain of the films also increased with the addition of LA, although the tensile strength decreased slightly compared to pure PHB/S. Overall, the results of this study provide baseline information on the improvement of PHB-based bioplastics.